Fatal pulmonary thromboembolism after prolonged physical immobilization in hospitalized psychiatric patients - Stefanović Vesna; Kuzmanović Ana; Stefanović Slaviša (Vojnosanitetski Pregled)
Background/Aim. Pulmonary thromboembolism (PTE) may be one of the causes of sudden death in hospitalized psychiatric patients. The aim of our study was to investigate whether fatal PTE in these patients may be the result of their prolonged physical immobilization, particularly when there were associated risk factors, and to emphasize the importance of this problem. Methods. A retrospective analysis of medical records of psychiatric patients died suddenly at the Department of Intensive Care of the Clinic of Psychiatry “Dr Laza Lazarevic”, Belgrade, in the period January 1, 2010 - December 31, 2011, was performed. Data of those for which the autopsy showed PTE as the immediate cause of death were extracted, and the presence of risk factors for the development of deep vein thrombosis analyzed. Results. In the observed period, out of 4,001 hospitalized psychiatric patients 53 died, and for 18 of them autopsy was required due to sudden death. In five patients, autopsy revealed PTE as a direct and sole cause of death. All the five patients were males, mean age 45.2 years, and during hospitalization all received strong antipsychotics and diazepam. Of the total duration of their hospital stay (mean 8.2 days), they were temporarily immobilized during an average 4.2 days. Four of them had acute infection, three were active smokers, and the two had a body mass index > 30 kg/m2. Conclusion. Our results suggest a possible link between prolonged physical immobilization of psychiatric patients who also receive antipsychotic therapy, and total PTE.